(3cJGH jJVef GdJfHjg Ydi cdGe dSjOi CHj GdMSf GdTGPdi aj Uag bGQF GdMRH GdcHjQs - (3CHh GdMSf GdTGPdjs
(3ChdgG (B:s
(3GdMeO ddg hHYO abO cGf HdZfi cJGH efce hCfJe JPcQhf ajg Cfce YGRehf Ydi bQGAI GdMRH GdcHjQ s
(3BNQgG (B:s
(3hQHfG YR hLd gh hdi GdJhajb dfG hdce Edi eG jMHg hjQVGg dGQH ZjQg hdG eYHhO ShGg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3eUOQ GbJfGA GdCUd (B:s
(3GdESchQjGd s
Keywords: (3GdJUha hGdBOGH GdTQYjIs